2017
DOI: 10.1097/pcc.0000000000001067
|View full text |Cite
|
Sign up to set email alerts
|

Electrographic Seizures in Children and Neonates Undergoing Extracorporeal Membrane Oxygenation

Abstract: Objective We aimed to determine the incidence and risk factors for electrographic seizures (ES) in neonates and children requiring extracorporeal membrane oxygenation (ECMO) support. Design Prospective quality improvement project. Setting Quaternary care pediatric institution. Patients Consistent with American Clinical Neurophysiology Society EEG monitoring recommendations, neonates and children requiring ECMO support underwent clinically indicated EEG monitoring. Interventions We performed a two-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 32 publications
6
63
0
Order By: Relevance
“…Electroencephalogram (EEG) is a non-invasive, well-tolerated study that can give dynamic information on cerebral functioning and provide insight into the risk of neurologic sequelae. A 2017 study by Lin et al looked at a series of 112 patients who received ECMO in which 88% underwent EEG [10]. They found favorable neurologic outcomes in those without seizures versus those with seizures and noted an increased risk of death associated with electrographic seizures [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electroencephalogram (EEG) is a non-invasive, well-tolerated study that can give dynamic information on cerebral functioning and provide insight into the risk of neurologic sequelae. A 2017 study by Lin et al looked at a series of 112 patients who received ECMO in which 88% underwent EEG [10]. They found favorable neurologic outcomes in those without seizures versus those with seizures and noted an increased risk of death associated with electrographic seizures [10].…”
Section: Introductionmentioning
confidence: 99%
“…A 2017 study by Lin et al looked at a series of 112 patients who received ECMO in which 88% underwent EEG [10]. They found favorable neurologic outcomes in those without seizures versus those with seizures and noted an increased risk of death associated with electrographic seizures [10]. Seizures during ECMO are associated with neurologic complications such as developmental delay, motor deficits, behavioral problems, and decreased quality of life scores [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Efficacy was not associated with the choice of first‐line ASM (PHB or LEV), but it was associated with seizure burden and underlying disease severity. Factors associated with less favorable response to first‐line ASM therapy included ECMO exposure and single‐ventricle defects, which are both independently associated with an increased risk of seizures 2,29,30 …”
Section: Discussionmentioning
confidence: 99%
“…Although less common than intracranial hemorrhage and stroke, seizures can be difficult to recognize if they are nonconvulsive or subclinical. A study of children and neonates undergoing ECMO revealed that 18% of patients had electrographic seizures, with 61% of those patients having electrographic status epilepticus and 83% having exclusively electrographic seizures [39]. Another recent study of neonatal and pediatric patients found electrographic seizures in 23% of their patients, especially within the first 24 hours of ECMO [40].…”
Section: Seizuresmentioning
confidence: 99%